Synthesis, characterization and antimicrobial activity of biodegradable conducting polypyrrole-graft-chitosan copolymer - Cabuk, M.; Alan, Yusuf; Yavuz M.; Unal H.I. (Elsevier B.V., 2014)
In this study, polypyrrole-graft-chitosan (PPy-g-CS) copolymer was chemically synthesized and its structural and morphological properties characterized by FTIR, UV-vis, SEM, XRD, TGA and zeta-potential techniques. The results revealed that there were strong interactions between PPy and CS chains. The electrical conductivity of CS increased to semiconducting range by grafting. The crystallinity and thermal stability of PPy-g-CS copolymer improved when compared to CS. The copolymer was tested against various bacterial and fungal strains at various concentrations and results obtained were compared with the reference antibiotics. The results indicated that the antibacterial activity of PPy-g-CS copolymer was stronger than CS and PPy alone. The antibacterial activity of the PPy-g-CS copolymer observed to increase with rising concentration, and showed stronger activity against bacteria than Penicillin (10 mg), Rifampicin (5 mg) and Trimethoprim (25 mg), whereas showed equipotent activity with Amikacin (30 mg) and Erythromycin (15 mg) antibiotics. © 2014 Elsevier B.V. All rights reserved.
Keywords: Antibacterial activity; Band gap; Chitosan; Graft copolymer; Polypyrrole